A study on the strategies of successful Bumiputra food service business in Kedah, Perlis and Penang: concept, food, ambience and business processes / Mohammad Zaki Ayob ... [et al.] - Ayob, Mohammad Zaki; Mohd Saman, Fatimah; Md Yusoff, Mohd Sukor; Abidin, Norridzwan (Universiti Teknologi MARA, Kedah, 2004)
Today, food service business operators are faced with dynamic wants of their customers. To survive, they need to ensure that their patrons are satisfied and remain loyal. Feedback is a crucial factor, and it is about time restaurant owners listen to their customers. A major step to move forward is to identify the key factors that would lead to customer satisfaction and loyalty. This research uses the structural equations modeling that link customer satisfaction to its causes and consequence. The causes of customer satisfaction (f/2) are perceived quality of "hardware" ({1), perceived quality of "software" ({2), and perceived value (f/1). Customer satisfaction is the intermediate variable for customer loyalty. The research conducted in the three northern states found that perceived product quality (hardware) had almost 80% total effect on customer satisfaction and about 69% total effect on customer loyalty. The variables of perceived product quality include customers' overall perceptions, food freshness, cleanliness, and taste. The "software" variables that affect customer perception and value are overall restaurant attractiveness, cleanliness, waiter responsiveness, table arrangements, order taking and delivery. Bumiputra restaurant operators should focus on the "hardware" aspects, as they are important determinants of customer satisfaction and key success factors of their businesses.